2017
DOI: 10.1002/ppsc.201600388
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Au36(SR)24 Nanoclusters for Photoluminescence Enhancement

Abstract: (1 of 6) 1600388The luminescence of metal nanoparticles constitutes an area of significant interest in recent years, in particular the luminescence of ultrasmall gold and silver nanoparticles. Gold has particular surface characteristics and low toxicity compared to other luminescent nanoparticles. However, gold often has weaker luminescence; thus, a major goal of research is to enhance gold nanoparticle luminescence. In this work, surface ligand engineering is performed on atomically precise Au 36 (SR) 24 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“… 1 , 2 , 8 , 17 24 Although several luminescent NCs have been reported, 8 , 18 , 21 31 most of them exhibit lower quantum yields (QYs) compared with other fluorescent nanomaterials (such as lanthanide nanoparticles, 32 organic dyes 33 and quantum dots 34 ), which severely impedes extensive application of fluorescent NCs in biological and sensing fields. Several strategies have been developed to enhance the PL QY of NCs, and they can be mainly classified into the following three categories: (1) tailoring the capping ligands of NCs (in terms of controlling the ligand to metal charge transfer (LMCT) process); 8 , 35 37 (2) controlling the metal composition in the NC kernel; 21 , 22 , 26 , 28 , 29 , 38 and (3) aggregation-induced emission (AIE) from non- or weakly luminescent metal NCs (or complexes). 19 , 20 , 25 , 39 , 40 Nowadays, the AIE strategy is being expanded to the hydrocarbon, metal complex, metal NC, and macromolecular research fields.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 8 , 17 24 Although several luminescent NCs have been reported, 8 , 18 , 21 31 most of them exhibit lower quantum yields (QYs) compared with other fluorescent nanomaterials (such as lanthanide nanoparticles, 32 organic dyes 33 and quantum dots 34 ), which severely impedes extensive application of fluorescent NCs in biological and sensing fields. Several strategies have been developed to enhance the PL QY of NCs, and they can be mainly classified into the following three categories: (1) tailoring the capping ligands of NCs (in terms of controlling the ligand to metal charge transfer (LMCT) process); 8 , 35 37 (2) controlling the metal composition in the NC kernel; 21 , 22 , 26 , 28 , 29 , 38 and (3) aggregation-induced emission (AIE) from non- or weakly luminescent metal NCs (or complexes). 19 , 20 , 25 , 39 , 40 Nowadays, the AIE strategy is being expanded to the hydrocarbon, metal complex, metal NC, and macromolecular research fields.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] To date, several recent studies have been reported aiming to produce AuNCs with enhanced luminescence, [13][14][15][16][17] and the mechanism behind high luminescence is now better explained. [18][19][20][21] Among all of the explanations, increasing the content and aggregation degree of Au (I)-thiolate complexes on the surface of Au(0) core has been widely accepted as an effective way to gain highly luminescent AuNCs through enhanced aurophilic interactions. [22,23] Besides, AuNCs can undergo aggregation-induced emission (AIE) mechanism that further enhances the PL intensity.…”
Section: Doi: 101002/ppsc201900314mentioning
confidence: 99%
“…However, the low quantum yield (QY) greatly limits their exploitation (typically ≈0.1%) . To date, several recent studies have been reported aiming to produce AuNCs with enhanced luminescence, and the mechanism behind high luminescence is now better explained . Among all of the explanations, increasing the content and aggregation degree of Au (I)‐thiolate complexes on the surface of Au(0) core has been widely accepted as an effective way to gain highly luminescent AuNCs through enhanced aurophilic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…40,41,43,46,53,58,61,62,74,80,125,130,138,147,149,159,162,166,197 888,890,891,915,916,922,932,936939 Furthermore, such ligandexchange reactions can be also used for size-selective synthesis of Au n (SR) m clusters, which are difficult to prepare directly. 46,53,61,62,80,138,149,159,264,301,306,467,484,491,515,571,628,633,637,662,744747,769,772,773,…”
Section: Estimation Of Heteroatom Substitution Positionmentioning
confidence: 99%